PENGARUH MEDIA GIMKIT TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR - Madani, Maghfiroh Sulthon; Putri, Dya Ayu Agustiana; Sari, Eka Yuliana (Universitas Negeri Surabaya, 2025)
This study examines the effect of using Gimkit learning media on the learning interest of elementary school students. Using a quantitative survey method, data were collected through a questionnaire given to 54 students. The results showed that the use of Gimkit had a significant positive effect on students' learning interest, with statistical analysis revealing a p-value of less than 0.001. These findings highlight the importance of interesting and interactive learning media in increasing students' motivation and participation in the learning process. This suggests that the application of innovative educational tools such as Gimkit can effectively improve students' learning interest and learning outcomes.